HUBUNGAN PENGETAHUAN DAN SUMBER INFORMASI DENGAN PELAKSANAAN SADARI DI SMAN BERNAS PANGKALAN KERINCI - Joria Parmin (Universitas Pahlawan Tuanku Tambusai, 2018)
Self Breast Examination (BSE) is a series of procedures to determine the presence of lumps or abnormalities in the breast early. According to the World Health Organization (WHO), around 8-9% of women have the potential to develop breast cancer. Breast cancer is the type most commonly found in women. Every year more than 250,000 new cases of breast cancer are diagnosed in Europe and approximately 175,000 in the United States. The purpose of this study was to determine the relationship of knowledge and information sources with the implementation of BSE in young women in BERNAS Pangkalan Kerinci Public High School in 2018. This type of research is quantitative with cross sectional design. The population in this study were students of class XI and XII in BERNAS Senior High School in Kerinci Base totaling 234 people. The sample in this study was 148 students taken by random sampling technique. The results of the study showed that some respondents who lackedknowledge about the Implementation of BSE 101 (68.2%), did not have 106 sources of information about BSE Implementation (71.6%). From this study it can be concluded that for respondents to always be aware and do BSE in order to detect breast cancer early.